Success rate of infrazygomatic miniscrews considering their design and insertion techniques. A review - Rodríguez-Rimachi, María Emely (2022)
Miniscrews offer the possibility of performing dental movements, minimizing unwanted side effects, and enhancing effectiveness. Extra-alveolar miniscrews are ideal as they provide excellent primary stability and avoid anatomical structures. However, in some cases, the primary stability is lost before achieving the success of the mechanics used and thus, the most likely causes of failure should be determined. The purpose of this review was to analyze the success rate of infrazygomatic miniscrews, considering their design and the insertion techniques used. Data collection of this literature review was carried out by searching PubMed, Wiley, Google Scholar sites, SCIELO, Elsevier, and Dialnet for publication made from 2003 to June 2022. The search was carried out on June 10th, 2022, and the following keywords were used; infrazygomatic crest, miniscrews, anchorage, and stability. Different topics were analyzed and discussed highlighting their clinical relevance. After analyzing the 798 articles, 566 were excluded. The remaining articles were reanalyzed and 153 articles were excluded for the title or abstract and 33 articles were excluded for the methodology. Finally, 46 items remained. After thoroughly analyzing all the articles included, this study concluded that the alloy of the miniscrew (stainless steel or titanium), perforation of the maxillary sinus, and the placement area (adhered mucosa or mobile mucosa) do not influence the survival of the miniscrew. The evidence also indicates that the percentage of failure is lower in infrazygomatic compared to intraradicular miniscrews. Orthodontists can confidently and safely include infrazygomatic miniscrew in different orthodontic procedures.